2013
DOI: 10.1136/gutjnl-2012-304190
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Paneth cell antimicrobial function is independent of Nod2

Abstract: Objective Although polymorphisms of the NOD2 gene predispose to the development of ileal Crohn's disease, the precise mechanisms of this increased susceptibility remain unclear. Previous work has shown that transcript expression of the Paneth cell (PC) antimicrobial peptides (AMPs) α-defensin 4 and α-defensin-related sequence 10 are selectively decreased in Nod2−/− mice. However, the specific mouse background used in this previous study is unclear. In light of recent evidence suggesting that mouse strain stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 43 publications
3
82
3
Order By: Relevance
“…Early studies suggested that mutant NOD2 alleles could produce defects in the production of some ␣-defensins from humans (17) and mice (18) and offered a mechanism to account for an altered microbial composition and inflammatory response in CD. However, the precise role of NOD2 in CD remains uncertain based on human (19,20) and better-controlled mouse studies (21) that show antimicrobial functions of Paneth cells are independent of NOD2 status. Other antimicrobial peptide classes, such as ␤-defensin 2 and ␤-defensin 3, are increased in inflamed Crohn's disease lesions (22,23), while the antimicrobial monokine MIG (monokine induced by gamma interferon) (24) and LL-37 are elevated in the mucosa of ulcerative colitis (UC) patients (25,26), suggesting that bacteria living at the mucosal surface with an active role in inflammatory bowel disease (IBD) pathogenesis would require mechanisms to resist antimicrobial peptide defenses in the inflamed gut.…”
mentioning
confidence: 99%
“…Early studies suggested that mutant NOD2 alleles could produce defects in the production of some ␣-defensins from humans (17) and mice (18) and offered a mechanism to account for an altered microbial composition and inflammatory response in CD. However, the precise role of NOD2 in CD remains uncertain based on human (19,20) and better-controlled mouse studies (21) that show antimicrobial functions of Paneth cells are independent of NOD2 status. Other antimicrobial peptide classes, such as ␤-defensin 2 and ␤-defensin 3, are increased in inflamed Crohn's disease lesions (22,23), while the antimicrobial monokine MIG (monokine induced by gamma interferon) (24) and LL-37 are elevated in the mucosa of ulcerative colitis (UC) patients (25,26), suggesting that bacteria living at the mucosal surface with an active role in inflammatory bowel disease (IBD) pathogenesis would require mechanisms to resist antimicrobial peptide defenses in the inflamed gut.…”
mentioning
confidence: 99%
“…A potential explanation for this finding is the regulation of β-defensin 2 by NOD2, the expression of which is inducible by the presence of commensal bacteria [69,81]. Still, other animal studies have suggested these microbial changes seen in NOD2-deficient mice are dependent on housing conditions, as similar changes were noted in wild type mice when cohoused with the NOD2-deficient mice [82,83]. Clearly, there is plentiful evidence to suggest a relationship between the gut microbiome and NOD2; however, more research will be needed to further determine the extent of this relationship and its importance.…”
Section: Genetic and Microbial Interactions In Inflammatory Bowel Dismentioning
confidence: 93%
“…However, this observation has been questioned by others, claiming that the reduced alpha-defensin expression is simply the consequence of inflammation and independent of NOD2 status [58]. Furthermore, in a recent study on C57BL/6 mice, NOD2 deficient animals presented with equivalent defensin levels and identical antimicrobial activity against commensal and pathogenic bacterial strains as their wild type littermates, and their gut microbial composition was also similar [59]. Nevertheless, other animal experiments have suggested distinct mechanisms connecting NOD2 deficiency to CD.…”
Section: Important Gene Loci In CDmentioning
confidence: 96%